O cotidiano escolar do professor coordenador: o diálogo entre teoria e prática - Souza, Reinaldo Ortiz de (2010)
The present dissertation describes, from a research realized in the Educational area and research line denominated Educational Institution: organization and management, the quotidian of the teachers who develop the rewarding function of Coordinator Teachers in the city of Presidente Prudente, São Paulo State, and it has got as aim to investigate, under the Resolution SE - 88, of 19-12-2007 light, the existence of contrasts between the legal performance and the practice developed in their quotidian. To reach the proposed aims, it was initially presented a historical review about the importance of the function of the pedagogical coordination in São Paulo State. After that we reflect about the Coordinator Teachers quotidian as implementers of necessary changes in getting good results. At the end, we present reflections about the continued formation of the teachers as the way of the construction of conceptions of a school in where all learn. The adopted methodology was the case study, which has, as main instruments for the data collection, the application of questionnaires and reflexive interviews in which from the Resolution SE 88, from 19-12-2007, the Coordinator Teachers offered data about their actuation in the schools. The description and analysis of the referred questionnaire enabled, from the speech of the subjects of the research, to trace scenery of the difficulties that the Coordinator Teachers present to realize an efficient work. These professionals have difficulty to evaluate the work developed in the schools and guarantee the participation of all segments in their actions. They also present doubts in how to realize the registers of the formation meetings in which the criteria for the selection of the adequate materials to the teaching action and, further, how to diagnose the knowledge of the teachers to continue their formation in service.